Causes of Death in Implant Patients Treated in the Edentulous Jaw: A Comparison between 2098 Deceased Patients and the Swedish National Cause of Death Register. (11th March 2019) - Kowar, Jan; Stenport, Victoria; Nilsson, Mats; Jemt, Torsten
Abstract : Background . Previous research has reported an association between tooth loss and patient mortality, while the cause of death has not been elucidated. Objective . The purpose was to describe and compare the cause of death in implant patients treated consecutively in the edentulous arch with a reference population. Methods . Altogether, 3902 patients were included between 1986 and 2014. Data on the causes of death for deceased patients were compared to the Swedish National Cause of Death Register for a comparable time period. Standardised mortality ratios (SMRs) were calculated based on gender and age and tested for statistical significance. Results . Most deceased patients (2, 098) died from diseases in the circulatory system (CVD; 42%) and from cancers (26%). SMR indicated a generally increased mortality (total group) compared to the reference population during inclusion (P < 0.05 ; 1986–2014). Patients treated early (1986–1996) showed a lower SMR compared to patients treated later (P < 0.05 ; 1997–2014) especially related to CVDs. Younger patients (<60 years at surgery) showed an increased mortality due to CVDs when treated late (1997–2014; SMR = 5.4, P < 0.05 ). Elderly patients (>79 years at surgery) showed a significantly lower mortality in almost all observed causes of death (1986–2014;P < 0.05 ) with also a significantly lower mortality due to CVDs during the early period (1986–1996; SMR = 0.3, P < 0.05 ). Conclusion . An overall increased mortality was observed for the edentulous implant patient compared to the reference population. Elderly patients (>79 years) showed significantly lower mortality for all causes of death independent of the time period of implant surgery. Younger patients (<60 years) present an increased risk for early mortality related to CVD. SMR for all causes of death increased for patients treated late (1997–2014) as compared to patients treated early (1986–1996).